Perilaku Menyontek Ditinjau dari Prokrastinasi Akademik pada Pelajar SMA Yos Sudarso - Charlie Sanlie; Winida Marpaung; Rianda Elvinawanty (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
The purpose in this study is to find out the relation between academic cheating and academic procrastinations. Academic procrastination is the act of someone who replaces the implementation of more important things with tasks that are not too important, or doing things that are more fun to do so that procrastinating important tasks to another day (Newton, 2014). The researchers assuming there was a positive relationship between variable academic cheating and academic procrastinations. Participants for this study collected by a disproportionate stratified random sampling method and the sample in this research are 139 students at SMA Yos Sudarso Medan. The correlation coefficient obtained was 0.562 (p<0.05). These results show that there is a absolute and significant relationship between academic cheating and academic procrastinations.